Possible Role of NUCB2/nesfatin-1 in Adipogenesis - Ramanjaneya, Manjunath; Addison, Melisande; S. Randeva, Harpal (Current Pharmaceutical Design, 2013)
NUCB2 and its proteolytically cleaved product nesfatin-1 were initially identified as hypothalamic neuroproteins that inhibit food intake, via a leptin-independent pathway. Since then recent studies have found NUCB2/nesfatin-1 to be expressed both centrally, as well as in peripheral tissues. The recent implementation of novel experimental approaches has produced a large body of evidence implicating NUCB2/nesfatin-1 in a diverse range of biological functions and in the modulation of food intake, energy homeostasis and metabolism. In this review, we discuss the discovery of NUCB2 and its proteolytic product nesfatin-1, and its expression in both central and peripheral tissues. In addition we shed light on the most recent discoveries supporting the role for NUCB2/nesfatin-1 in peripheral tissues and its association with metabolic alterations. Moreover, we highlight the importance of NUCB2 and nesfatin-1 in adipose tissue, its regulation of adipogenesis and obesity-associated metabolic diseases.
Keywords: obesity